An innovative educational program for addressing health disparities in translational cancer research. Issue 1 (5th November 2020) - Oldham, Carla E.; Gathings, M. J.; Devi, Gayathri R.; Patierno, Steven R.; Williams, Kevin P.; Hough, Holly J.; Barrett, Nadine J.
Abstract: North Carolina Central University (NCCU) and Duke Cancer Institute implemented an NCI-funded Translational Cancer Disparities Research Partnership to enhance translational cancer research, increase the pool of underrepresented racial and ethnic group (UREG) researchers in the translational and clinical research workforce, and equip UREG trainees with skills to increase diversity in clinical trials. The Cancer Research Education Program (C-REP) provided training for UREG graduate students and postdoctoral fellows at Duke and NCCU. An innovative component of C-REP is the Translational Immersion Experience (TIE), which enabled Scholars to gain knowledge across eight domains of clinical and translational research (clinical trials operations, data monitoring, regulatory affairs, UREG accrual, biobanking, community engagement, community outreach, and high-throughput drug screening). Program-specific evaluative metrics were created for three broad domains (clinical operations, basic science/lab research, and population-based science) and eight TIE domains. Two cohorts ( n = 13) completed pre- and post-surveys to determine program impact and identify recommendations for program improvement. Scholars reported statistically significant gains in knowledge across three broad domains of biomedical research and seven distinct areas within TIE. Training in translational research incorporating immersions in clinical trials operation, biobanking, drug development, and community engagement adds value to career development of UREG researchers.